2020
DOI: 10.31703/gssr.2020(v-i).19
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Quality Culture and Core Practices of Quality Management System and their Direct and Indirect Effects on Organizational Performance

Abstract: This research work empirically assesses the relationship between the Quality Culture (QC) practices and core practices of Quality Management System (QMS) and investigates their direct and indirect influences on organizational performance. Data for this research work is collected from 80 Technical Services Organizations of Pakistan through mail survey and the proposed framework and hypotheses have been examined through Structural Equation Modelling. The results of hypotheses show that synergies among QCPractice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This implies that we could find a statistically significant association between organizational compensation policy and employee's motivation and commitment but not with employee's KSAs, likewise, between selection policy and employee's KSAs but not with employee's opportunities to contribute. It is also worth noting that, while we conceptualize specific HR policies within each domain, a single HR policy may be associated with multiple HR policy domains (Peccei & Voorde, ;Rehmani et al, 2020b). For instance, although training is rationally linked to employees' KSAs, it can also serve as a source of incentive for employees, particularly when used as a reward (Jyoti et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This implies that we could find a statistically significant association between organizational compensation policy and employee's motivation and commitment but not with employee's KSAs, likewise, between selection policy and employee's KSAs but not with employee's opportunities to contribute. It is also worth noting that, while we conceptualize specific HR policies within each domain, a single HR policy may be associated with multiple HR policy domains (Peccei & Voorde, ;Rehmani et al, 2020b). For instance, although training is rationally linked to employees' KSAs, it can also serve as a source of incentive for employees, particularly when used as a reward (Jyoti et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, one of the most critical problems the manufacturing SMEs face in Pakistan is poor inventory management and control due to ineffective inventory forecasting, inadequate record-keeping, and misalignment of sales and demand curves [ 39 , 40 ]. Abbas [ 41 ] also indicated that lack of inventory management expertise had hindered small and medium-sized manufacturing companies from becoming powerful rivals in the manufacturing sectors.…”
Section: Discussionmentioning
confidence: 99%
“…In operational management literature, no set threshold level determines the effectiveness of a construct; generally, optimum effectiveness levels are achieved through an optimum combination of inputs (management practices, capital, resources, etc.) [ 26 ]. The current study uses an optimum level of 80% of each 'construct's degree of applicability [ 27 , 28 ].…”
Section: Methodology Of Validation Frameworkmentioning
confidence: 99%